2017
DOI: 10.21609/jiki.v10i1.372
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Graphology and Enneagram Techniques in Determining Personality Type Based on Handwriting Features

Abstract: This research was conducted with the aim of developing previous studies that have successfully applied the science of graphology to analyze digital handwriting and characteristics of his personality through shape based feature extraction, which in the present study will be applied one method of psychological tests commonly used by psychologists to recognize human's personality that is Enneagram. The Enneagram method in principle will classify the personality traits of a person into nine types through a series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…The current accuracy rate stands at 85.7%. This accuracy value demonstrates an improvement compared to previous research conducted in 2017, where the accuracy increased by 4.1%, from 81.6% [6]. Consequently, this study concludes that the application of Invariant Moment as a descriptor or feature value for handwriting pattern recognition enhances accuracy by 4.1% compared to the utilization of ROI descriptors with the same amount of final test data.…”
Section: Resultssupporting
confidence: 45%
See 3 more Smart Citations
“…The current accuracy rate stands at 85.7%. This accuracy value demonstrates an improvement compared to previous research conducted in 2017, where the accuracy increased by 4.1%, from 81.6% [6]. Consequently, this study concludes that the application of Invariant Moment as a descriptor or feature value for handwriting pattern recognition enhances accuracy by 4.1% compared to the utilization of ROI descriptors with the same amount of final test data.…”
Section: Resultssupporting
confidence: 45%
“…This was achieved through an application developed to implement feature extraction. The handwriting patterns of the 120 reference data encompass various combinations of Baseline, Breaks, Slant, and Size, which were previously mapped to enneagram types in the studies conducted in the previous year [5] [6]. From these patterns, feature values were extracted and averaged to create reference patterns for determining personality types from the test data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…• Fallah et al [12] developed a solution to characterise the personality of the author of a piece of handwritten text by combining image processing and pattern recognition techniques, with the reference provided by the MMPI personality test. • In the same field, Pratiwi et al [13] concluded that there is a correlation between the analysis of personality based on psychology and graphology, and that the results coincide with the personality types for 81.6% of the cases studied. • Miguel et al [14] studied the extent to which the handwritten signature can reveal information about a person.…”
Section: Related Workmentioning
confidence: 94%